(untitled) (MAUSAM, 2001)
A method of testing the significance of Z- Statistic is introduced in this paper to discern the role of Convective Available Potential Energy (CAPE) and Convective Inhibition Energy (CINE) in forecasting the occurrence of pre-monsoon thunderstorms over Gangetic West Bengal (GWB). The result reveals that a negative correlation exists between CAPE and CINE. It further indicates that a range for the lower values of CINE can be fixed where the frequency of occurrence of such storms will be maximum, but such range, either for lower or for higher values of CAPE, is not possible. The paper, thus, ends with a very interesting finding that a measure of CINE is the only relevant parameter whereas CAPE has no significant role in forecasting the occurrence of pre-monsoon thunderstorms over GWB, which is in contrast to the concept of severe thunderstorms of Great Plains of America.